ChemInform Abstract: Polyhydroxyamino‐Piperidine‐Type Iminosugars and Pipecolic Acid Analogues from a D‐Mannose‐Derived Aldehyde. Issue 9 (March 2015) - Matassini, Camilla; Mirabella, Stefania; Ferhati, Xhenti; Faggi, Cristina; Robina, Inmaculada; Goti, Andrea; Moreno‐Clavijo, Elena; Moreno‐Vargas, Antonio J.; Cardona, Francesca
Abstract Straightforward strategies for the synthesis of diversely functionalized polyhydroxy and polyhydroxyamino piperidines are presented, starting from aldehydes (I) or (V).